Steindl's analysis of firm growth and the tendency toward industry concentration - Bloch, Harry (Routledge, 2005)
A recurring theme in Steindl's analysis of firm growth is the tendency toward industry concentration. His earliest writings examine the influence of risk on firm growth (Steindl (1941, (1945a) and (1945b)). He then turns his attention to the influence of technical progress ( Steindl (1976), and, finally, to the influence of random processes (Steindl (1965)). In each of these analyses there emerges a tendency toward the concentration of industry.Steindl takes the concentration of industry to be an established fact of mature capitalism and sees his analysis as providing an explanation for this fact. The same analysis provides the basis for the behavior patterns attributed to oligopolistic firms. He then examines the implications of the oligopolistic pricing and investment behavior for macroeconomic performance (Steindl (1976), (1979) and (1989)). The analysis of firm growth thus provides the foundation for Steindl's understanding of mature capitalism. The present essay examines Steindl's analysis of firm growth and evaluates his explanation of industry concentration.